Landscapes of Housing - Nevena Novaković (Docomomo Journal)
The concepts of residential space and housing, created by Yugoslav modernist Juraj Neidhardt through the collaboration with architect Dušan Grabrijan, have yet to be investigated systematically, especially from the urban design point of view. As rooted in joint ethnographic research of local Bosnian dwelling culture and vernacular architecture, Neidhardt developed a specific approach to modern neighborhood design compared to the prevalent scientific-planning approach in post-war modernism. From the perspective of urban design, Neidhardt examined the possibilities of conceptualizing more humane dwellings in the context of rapid housing construction in post-war Yugoslavia and Bosnia and Herzegovina, looking through the lens of traditional dwelling culture in which architecture is a mediator between man and landscape. The article will distill, describe, and interpret Neidhardt’s ideas of a modern neighborhood that arise from elaborated descriptions of the Bosnian vernacular architecture articulated in close collaboration with Dušan Grabrijan. Neighborhood concepts have significantly different densities and forms, as designed and redesigned through four decades. Nevertheless, the fundamental design principles common to all neighborhood concepts are recognized, focusing on the dichotomy of architecture and landscape in terms of form and meaning. The research was based on analyzing the author’s books and published texts and designs in several Yugoslavian architectural journals.